2011
DOI: 10.1177/0960327111417269
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin mediates apoptosis in human nasopharyngeal carcinoma NPC-TW 039 cells through mitochondrial depolarization and endoplasmic reticulum stress

Abstract: Capsaicin, a pungent compound found in hot chili peppers, has been reported to have antitumor activities in many human cancer cell lines, but the induction of precise apoptosis signaling pathway in human nasopharyngeal carcinoma (NPC) cells is unclear. Here, we investigated the molecular mechanisms of capsaicin-induced apoptosis in human NPC, NPC-TW 039, cells. Effects of capsaicin involved endoplasmic reticulum (ER) stress, caspase-3 activation and mitochondrial depolarization. Capsaicin-induced cytotoxic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 37 publications
1
46
0
3
Order By: Relevance
“…Most of the cytotoxic anticancer agents in present use have been shown to induce apoptosis in cancer cells such as etoposide, capsaicin, berberine, gomisin N and doxorubicin (Ghobrial et al, 2005;Wong, 2011). The anti-cancer drug etoposide is able to induce caspase-8 processing and apoptosis in cancer cells, capsaicin induces apoptosis through cellular stress, involving mitochondria and endoplasmic reticulum in several human cancer cells, berberine, an isoquinoline alkaloid, has several pharmacological properties and can affect in different levels the mitochondrial functions, gomisin N , a dibenzocyclooctadiene lignan, isolated from Schizandra chinensis Baill induced apoptosis of human leukemia U937 cells and doxorubicin also induces apoptosis in many cancer cells (Kim et al, 2010;Liu et al, 2011;IP et al, 2012). In apoptotic pathways, the Bcl-2 family of proteins are significant regulators of apoptosis and include both anti-apoptotic members (such as Bcl-2, Mcl-1, survivin and Bcl-xL) and pro-apoptotic members (for example, Bax, Bak, Bad, Bid, and Bik) (Wong, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cytotoxic anticancer agents in present use have been shown to induce apoptosis in cancer cells such as etoposide, capsaicin, berberine, gomisin N and doxorubicin (Ghobrial et al, 2005;Wong, 2011). The anti-cancer drug etoposide is able to induce caspase-8 processing and apoptosis in cancer cells, capsaicin induces apoptosis through cellular stress, involving mitochondria and endoplasmic reticulum in several human cancer cells, berberine, an isoquinoline alkaloid, has several pharmacological properties and can affect in different levels the mitochondrial functions, gomisin N , a dibenzocyclooctadiene lignan, isolated from Schizandra chinensis Baill induced apoptosis of human leukemia U937 cells and doxorubicin also induces apoptosis in many cancer cells (Kim et al, 2010;Liu et al, 2011;IP et al, 2012). In apoptotic pathways, the Bcl-2 family of proteins are significant regulators of apoptosis and include both anti-apoptotic members (such as Bcl-2, Mcl-1, survivin and Bcl-xL) and pro-apoptotic members (for example, Bax, Bak, Bad, Bid, and Bik) (Wong, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Capsaicin inhibited cell growth and promoted apoptosis on A375 cell line on human melanoma 37,39 . Anticancer activity of capsaicin against pancreatic cancer has successfully evaluated on PANC-1 cell line where it induced G0/G1 phase cell cycle arrest and apoptosis and ultimately arrest tumour growth 32,[40][41] .…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
“…Human esophageal epidermoid carcinoma also cured by capsaicin worked on CE 81T/VGH cell lines and found that it induced apoptosis and G0/G1 phase cell cycle arrest 37 . Capsaicin inhibited cell growth and promoted apoptosis on A375 cell line on human melanoma 37,39 .…”
Section: Anti-diabetic Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, capsaicin is proved to have good activity for inhibiting various tumor cells [2]. Besides, capsaicin also decreased the growth of human leukemic cells [3], gastric [4], nasopharyngeal [5], prostate [6], and hepatic carcinoma cells [7] in vitro because of its ability to mediate cell cycle arrest and induce cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%